Structure and Magnetic Properties of Yttrium-Doped M-Type Strontium Ferrite - Niu1, Xiao-Fei; Zhang1, Ming-Yu (Asian Journal of Chemistry, 2014)
In this paper we have prepared yttrium-doped M-type strontium ferrite SrYxFe(12-x)O19 (x = 0, 0.25, 0.5, 0.75, 1) calcined materials by solid-phase sintering method at 1150 °C for 3 h. Then the calcined materials were pressed for magnets under the condition of oriented magnetic field and sintered in 1295 °C for 3 h. We have used X-ray diffraction, scanning electron microscope and magnetic tester analyze the phase structure of the sintered magnets, the surface morphology of the sintered magnet and the magnetic properties of the sintered magnets, respectively. The results showed that with the increase of yttrium-doped, the lattice constant ‘a’ increases first of all and then decreases ‘c’ increases slowly, a/c first increases and then decreases, crystal X-ray density dx-ray approximation increases linearly. SEM showed that the magnet has prepared a typical hexagonal structure morphology. Magnetic studies showed that with the doping of yttrium increase, the remanence Br increasing monotonically, intrinsic coercivity Hcj and maximum energy product (BH)max and coercivity magnetic induction Hcb are first increases and then decreases. When the x = 1, have the maximum remanence Br with 420.7 mT, but the intrinsic coercivity Hcj decreases to a minimum value; when x = 0.75 the intrinsic coercivity Hcj have a maximum value of 323.7 KA·m-1 and the remanence Br reach 410.4 mT.